Formation of hollow carbon nanoshells from thiol stabilised silver nanoparticles via heat treatment. (November 2018) - Watts, Julie A.; Fay, Mike W.; Rance, Graham A.; Brown, Paul D.; Khlobystov, Andrei N.
Abstract: Uniform, < 10 nm sized, hollow carbon nano-shells (HCNS) have been prepared via a single-step, thermal treatment of alkanethiol stabilised Ag nanoparticles (TS-AgNP). Direct evidence for the formation of spherical HCNS from TS-AgNP is provided by in situ MEMS heating on Si3 N4 supports within a TEM, and ex situ thermal processing of TS-AgNP on carbon nanotube supports. A mechanism is proposed for the thermally driven, templated formation of HCNS from the TS-AgNP stabilising layer, with Ag catalysing the graphitisation of carbon in advance of thermally induced AgNP template removal. This facile processing route provides for excellent size control of the HCNS product via appropriate AgNP template selection. However, a rapid rate of heating was found to be crucial for the formation of well-defined HCNS, whilst a slow heating rate gave a much more disrupted product, comprising predominantly lacy carbon with decreased levels of graphitic ordering, reflecting a competition between the thermal transformation of the TS-layer and the rate of removal of the AgNP template. Graphical abstract: Bright field, diffraction contrast TEM micrographs of (a) TS-AgNP/Si3 N4 before rapid in situ heating to 850 °C (TP-1); and (b) the resultant HCNS, imaged at 850 °C. Image 1